2018
DOI: 10.1080/02656736.2018.1427287
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation of the biliary tree:in vivoproof of concept as potential treatment of unresectable cholangiocarcinoma

Abstract: The temperature distribution obtained through LA proved to induce a safe and effective intraductal coagulative necrosis of biliary ducts. These results represent the basis for further experiments on tumour-bearing models for the treatment of obstructive cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The problem of thermal injury to the bile ducts is also discussed in the context of radiofrequency ablation (RFA) of malignant hepatic lesions. 32 Just like MES, RFA relies on the effects of HF electrical current, which, apart from causing a significant temperature rise at the site of its application, also results in thermal injury to the bile ducts in the vicinity of the lesion. 33 Preserving the bile ducts and the surrounding structures from thermal damage and the investigation of intraluminal thermometry methods are actual issues of modern oncology.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of thermal injury to the bile ducts is also discussed in the context of radiofrequency ablation (RFA) of malignant hepatic lesions. 32 Just like MES, RFA relies on the effects of HF electrical current, which, apart from causing a significant temperature rise at the site of its application, also results in thermal injury to the bile ducts in the vicinity of the lesion. 33 Preserving the bile ducts and the surrounding structures from thermal damage and the investigation of intraluminal thermometry methods are actual issues of modern oncology.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, endoscopic radiofrequency ablation has been introduced into clinical use to palliate unresectable cholangiocarcinoma 1 2 ; however, it has not been possible to perform this technique under direct visualization. A preclinical study has been reported on laser ablation in the biliary system 3 . A few authors have also reported using intraductal cholangioscopy-guided laser dissection for benign pancreatic/biliary ductal strictures 4 5 .…”
Section: Figmentioning
confidence: 99%
“…Among them, stands Laser Ablation (LA), which exploits the absorption of laser light by the tissue to increase the temperature and thus to induce the cellular necrosis. 4,5 In the specific case of liver or of other deep-laying organs, minimally invasive LA procedures can be implemented by delivering the laser beam through a miniaturized optical fiber applicator inserted in the skin via a needle.…”
Section: Introductionmentioning
confidence: 99%